A Derridean sojourn on the Heideggerian path of Es gibt (reading of the eleventh session of Donner le temps II) - Ferrero Carracedo, Luis (Escritura e Imagen, 2023)
This paper is an inquisitive, questioning, meditative and also recreating reading of the eleventh session of the second part of the Seminar on the gift and time that Jacques Derrida gave in 1978-1979. Taking the Letter on Humanism (1946) as its center, as a vantage point, as a place of embarkation, Derrida carries out in this session an illuminating and critical task of the look that Heidegger projects, upstream, on Being and Time (1927) in around the German idiomatic expression Es gibt, which in the path of his thought acquired more and more prominence until reaching Time and Being (1962). In this reading, which is truly a reading of a reading, the aim is to unravel that first moment, upstream, of Derrida’s approach to a theme deeply related to the gift, an impossible possible that, like other great undecidables, mark, define, the Derrida’s work.